THE INTERPRETATION OF SEAT FACILITY’S FORM AND FUNCTION IN KARMAWIBHANGGA RELIEF OF BOROBUDUR TEMPLE - Sunarmi Sunarmi; Kusmadi Kusmadi; Sumarno Sumarno (Universitas Sebelas Maret, 2017)
The paper entitled “The interpretation of seat facility’s form and function in Karmawibhangga Relief of Borobudur Temple” was the result of the 1st stage of Competitive Grant Research entitled “The Development of Javanese Furniture Form as the Attempt of Solidifying and Preserving Local Culture in Surakarta”. The problem raised was what are form and function of seat facilities in Karmawibhangga Relief of Borobudur Temple including: (1) the form seems visually to be: bantalan (pad), amben kaki empat (four-leg bed), amben kaki enam (six-leg bed), amben kaki delapan (eight-bed bed), chair, and recess or throne. (2) The size of seat can be seen based on the strips forming a wide high plane, the form manifested intended to sitting in group or individually, social status, and material. (3) The furniture material can be seen based on size thickness and working technique indicating the presence of wood and stone material. (4) The technique used to finish the seat and to create profile indicated the presence of chiseling and lathing techniques. The seating had physical, personal, and social functions. The physical function of seat was manifested into form according to activity. The personal function of seat was manifested into the consideration of what for it is produced (intention of production) based on the difference of social status as could be seen in the different forms and size. The social function of seat was manifested into various complicated (ngrawit) forms, sizes, ornaments, and profile; the form was manifested proportionally between ornament, size, and technique indicating the presence of intellectuality in high art taste proving the presence of civilization.